Mga kagamitang panturo para sa indibiduwalisadong paglinang ng mga kasanayan sa pakikinig ng mga mag-aaral ng Pilipino/Filipino sa ika-4 na baitang ng mababang paaralan (Kaligirang pangalawang wika) - Madera, Clotilde A. 1944- (1977)
This study was conducted to help solve the pressing problem of the lack of aural discourse materials in Filipino in schools. This study dealt with two phases of the system of material designs: the design and development phases. The results of the evaluation provided the material writer enough basis for the modification and revision of the experimental materials.
Appendices: leaves 146-358
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Audio-lingual method (Language teaching).; Pilipino language -- Study and teaching (Elementary).; Teaching -- Aids and devices